Assessment of poly(methacrylic acid-co-N-vinyl pyrrolidone) as a carrier for the oral delivery of therapeutic proteins using Caco-2 and HT29-MTX cell lines - Carr, Daniel A.; Peppas, Nicholas A. (Journal of biomedical materials research. Part A, 2010)
Hydrogels of poly(methacrylic acid‐co‐N‐vinyl pyrrolidone) were synthesized and evaluated for their use as carriers for oral protein delivery. Insulin loading efficiencies were determined to be near 90% for carriers crosslinked with ethylene glycol dimethacrylate with corresponding weight incorporation levels near 12%. Although no insulin was released in gastric conditions, as desired, near instantaneous release occurred when the pH was raised to values typical of the intestinal area. Cytocompatibility studies with Caco‐2 and Caco‐2/HT29‐MTX cultures demonstrated that microparticles did not elicit toxic effects at concentrations up to 5.0 mg/mL. Insulin transport studies revealed that the carriers did not disrupt the cell layer and thus did not change the insulin permeability in the apical‐to‐basolateral direction. Therefore, microparticles of this system were best suited for oral delivery of therapeutic agents that do not require transport facilitation. © 2009 Wiley Periodicals, Inc. J Biomed Mater Res, 2010